P PENINGKATAN KEMAMPUAN LITERASI KEUANGAN, MANAJEMEN PEMASARAN BERBASIS DIGITAL DAN KOMUNIKASI BERBAHASA INGGGRIS SEBAGAI UPAYA REVITALISASI PEREKONOMIAN PARIWISATA DI PANTAI RUMBIA - Pebisitona Mesajaya Purba; Nikolas F. Wuryaningrat; Ismail; Supriyanto; Irvandi Waraney Ombuh (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Rumbia Beach in Minahasa Regency has promising tourism potential but faces challenges in financial management and marketing that impact suboptimal local economic contributions. This community service program aims to enhance the capacity of Village-Owned Enterprise (BUMDes) Jaya Desa Rumbia managers in financial literacy, digital marketing management, and English communication to revitalize the tourism economy. The implementation method encompasses six stages: proposal development, socialization through FGD, training with pre-test and post-test evaluation, digital technology implementation, intensive mentoring for three months, and establishment of business groups for program sustainability. The program involved Village-Owned Enterprise (BUMDes) managers with three main training components. Results demonstrate substantial improvements in financial literacy with the implementation of Kledo application that enhanced financial recording accuracy; digital marketing management experienced substantial improvement with the launch of website and social media that drove increased tourist visits; English proficiency improved with high satisfaction levels among foreign tourists. International tourist visits increased by 31,7 following the program. Recommendations include: continuous training with higher frequency, consistent digital content development, periodic refresher training programs, English club establishment, and replication of the intervention model to similar tourism destinations to maximize the economic impact of community-based tourism. This program successfully created transformation in tourism destination management that is more professional and sustainable.